MIMO Radar Space-Time Adaptive Processing for Multipath Clutter Mitigation - Mecca, V.F.; Ramakrishnan, D.; Krolik, J.L. (Fourth IEEE Workshop on Sensor Array and Multichannel Processing, 2006, 2006)
This paper describes a multiple-input-multiple-output (MIMO) generalization of space-time adaptive processing (STAP) to mitigate radar clutter subject to multipath propagation between transmit and receive arrays. Multipath clutter can occur when surface returns are multiply scattered, causing significant Doppler frequency and wavenumber spreads. In the worst case, multipath propagation may cause Doppler spread clutter to return via the receiver mainlobe. In such situations, conventional STAP cannot mitigate Doppler spread mainlobe clutter without also suppressing the target. MIMO radar techniques using orthogonal waveforms have been proposed for increasing radar coverage rate often at the expense of employing significantly larger radar time-bandwidth products. In this paper, we consider a MIMO approach wherein conventional radar waveforms are phase-coded to be orthogonal after Doppler processing at the receiver, i.e. in "slow-time". Slow-time MIMO has the advantages of being bandwidth efficient and easily implemented without the need to modify the receiver before range pulse-compression. In this paper, the mathematical formulation of MIMO STAP is developed for both direct-path and multipath clutter scenarios. At each slant range, the MIMO STAP processor operates on a receive sensor, transmitted pulses, and slow-time phase code channel data cube. Coherent combination of the decoded slow-time channels at the receiver permits effective control of the transmit array pattern by receive post-processing as a function of slant range. Simulation results demonstrate SNR gains when a transmit null is steered in the outbound direction towards the multiply scattered clutter.